Reklama społeczna w Polsce po 1989 roku - Czyhin, Borys (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2005)
Advocacy advertising is a special form of communication. There are opinions that its very definition is oxymoronic in nature. Its tools and methods are drawn from the repertoire of commercial marketing, yet the goals and the message are lofty and noble. The differences between commercial and advocacy advertising are subtle as they refer to the fundamental principles and measures of efficiency. The approach to strategy planning and creating the message of advocacy advertising is not professional in Poland. Advertising agencies do not employ social psychologists. The errors that emerge as a result are reflected in low efficiency of the messages. Advocacy advertising is a tool of sociotechnology. Its purpose is to shape the socially desirable attitudes and behaviors. Even the best intentions of the authors and orderers of advertising, however, cannot overcome the obstacle of limited budgets allocated to the socially committed marketing.
Advocacy Advertising in Poiand after 1989